KARAKTERISTIK SUKROSA ESTER DARI METIL MIRISTAT MENGGUNAKAN KATALIS K2CO3 dan Na2CO3 - Rahmadanis Rahmadanis; Erliza Hambali; Obie Farobie (Jurnal Teknologi Industri Pertanian, 2023)
Sucrose ester is a renewable raw material that is environmentally friendly, non-toxic, biocompatible, and biodegradable with emulsification, stabilizing, and conditioning characteristics, so it is widely used in emulsion product applications. This study aims to characteristics the sucrose ester from methyl Myristic using K2CO3 and Na2CO3 as catalysts. The synthesis of sucrose ester uses methyl Myristic, which is a renewable raw material. Synthesis of methyl myristic was carried out by the esterification method, the synthesis of sucrose ester was carried out by the transesterification method with free solvent, the catalyst used was alkaline K2CO3 and Na2CO3 (6%), the reaction was carried out at 60°C for 30 minutes then 110°C for 90 minutes. The analyzes carried out were FTIR, HPLC, pH, foam stability, emulsion stability, surface tension, interfacial tension, contact angle, particle size, and polydispersity index. The results showed the characteristics of sucrose ester using K2CO3 were better than Na2CO3. The resulting characteristics are the sucrose ester group present at a wave number of 1726 nm, sucrose ester content 96,87%; the pH 10.73, foam stability 88,06%, the emulsion stability 63,68%, the surface tension 29.64 cm/dyne, interfacial tension 2,96 cm/dyne, contact angle 36,85°, particle sizes in the range of 2,35-9,74 µm, and a polydispersity index value 0.412. The resulting sucrose myristate can be applied to the cleaning, personal care, and cosmetic industries Keywords: catalysts, methyl myristic, sucrose ester